Preparation and characterization of aluminum-air battery / Luqman Hakim Hendon. - Hendon, Luqman Hakim (2008)
An aluminum-air battery was fabricated using aluminum metal foil as the anode; potassium hydroxide (KOH) in hydroponics gel was used as the electrolyte. Commercial manganese-based as the air cathode, the air cathode consists of laminated structures of fibrous carbon dispersed with a manganese catalyst and supported by a nickel mesh. The air side consists of Teflon layer. The electrolyte was put into a cell holder. The potassium hydroxide with 3M has been chose as the electrolyte. The fabrications of aluminum-air battery were characterized according to their open circuit voltage OCV. Lastly, the batteries were analysed according to their self-discharge. The highest voltage produced was 1.5 V. After the reaction, it has been found that the corrosion of aluminum into AI2O3 occured on the aluminum foil anode.